Relasi Pertukaran Sosial antara Masyarakat dan Partai Politik - Nofal Liata (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
The study aims to discuss the social exchange relationship "symbiotic mutualism" mutual benefit between society and political parties. The author sees, the community's perspective saw political activity it is still perceived as something dirty, tends to apathy, not as a means of political struggle to make a profit. The purpose of this study is to uncover more conceptual facts of favorable relationships to two parties so that political activity is then a place of healthy and conducive struggle, which is not contrary to the rules of the law. The method of collecting data in this study is to use the primary data of political sociology core literacy, then to use secondary data on the relevance of social reality to strengthen primary data. This study of the symbiotic mutualism relationship is very beneficial to build the political awareness of the community and the elite of political parties to support development, whether it is the development of material and non-material, so that political activities become beneficial for all circles, not even in the left.